The relationship between eHealth literacy, social media self-efficacy and health communication intention among Chinese nursing undergraduates: A cross-sectional study - Sun, Huiping; Qian, Lin; Xue, Mengxin; Zhou, Ting; Qu, Jiling; Zhou, Jingxin; Qu, Junchao; Ji, Siqi; Bu, Yuan; Hu, Yicheng; Wu, Shaung; Chen, Yuhui; et al. (Frontiers in Public Health, 2022)
Background: With the popularization of the Internet, it has become possible to widely disseminate health information via social media. Medical staff’s health communication through social media can improve the public’s health literacy, and improving the intention of health communication among nursing undergraduates is of great significance for them to actively carry out health communication after entering clinical practice. Objective: To explore the relationship among eHealth literacy, social media self-efficacy, and health communication intention and to determine the mediating role of social media self-efficacy in the relationship between eHealth literacy and health communication intention. Design: A cross-sectional descriptive correlation design was used in this study. Participants: Stratified cluster sampling was used to select 958 nursing students from four nursing colleges in Jiangsu Province, China, from June to July 2021. Methods: Data were collected using the eHealth Literacy Scale, the Social Media Self-efficacy Scale, and the Health Communication Intention Questionnaire. Sociodemographic data were also collected. Correlation analysis and regression analysis were used to determine the relationship between eHealth literacy, social media self-efficacy, and health communication intention. Results: Health communication intention is positively correlated with eHealth literacy and social media self-efficacy. eHealth literacy directly affects the intention of health communication significantly (p < 0.001), and social media self-efficacy played a mediating role in the influence of eHealth literacy on health communication intention (the mediating effect accounted for 37.2% of the total effect). Conclusion: Improving the eHealth literacy of nursing undergraduates can directly affect or promote health communication intention and can also indirectly improve health communication intention through improving social media self-efficacy. In view of these results, targeted educational programs must be developed to improve eHealth literacy and social media self-efficacy among nursing undergraduates, thereby promoting their health information transmission.